Expediente - Araújo, Everaldo Lima de; Mendes, Thales Sant'Ana Ferreira; Lopes, Thiago Wallace dos Santos (Palimpsesto - Revista do Programa de Pós-Graduação em Letras da UERJ, 2020)
Expediente do número 31.